“ABU YAZID AL-BUSTAMI” (Riwayat Hidup dan Konsep Ajarannya) - Sulman Sulman (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Concept is an abstraction of an idea or mental image, which is expressed in a word or symbol, the concept is also expressed as part of knowledge built from various characteristics. Doctrine is everything that is taught; advice; The teachings of Abu Yazid were the first Sufi to carry the teachings of al-fana, al-baqa, and ittihad, which is a teaching on the concept of nullifying oneself (body), in which spiritual consciousness is eternal when united with Him